I costi della sepsi in Italia - Lucioni, C.; Currado, I.; Langer, M.; Mazzi, S. (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
The aim of this study is to evaluate additional hospitalisation costs and intangible costs (mortality) in patients with sepsis (intended as severe sepsis or sepsis shock) in Italy. The evaluation is based on clinical data from the Italian Sepsis Study, a prospective, multicentre study conducted in 99 Intensive Care Units (ICUs)located across Italy. Each ICU enrolled the first two (or three) patients admitted each month, during the year April 1993 to March 1994. In particular, data collected included the Average Length Of Stay (ALOS) in ICU and later in the regular ward, and the mortality within four weeks and in hospital. Out of the 2,946 patients enrolled, 2,641 never developed sepsis and were considered as the control group (comparability was confirmed based on gender, age, and comorbidity). The additional (respective to the control group) ALOSs of the patients with sepsis were valued in monetary terms using per diem full costs, inflated to 2000: 1,033.43 Euro for l day in ICU (published data) and 299.54 Euro for l day in the regular ward (estimated data based on published materials). Statistical significance was tested with Student t test. The hospitalisation cost of a patient with sepsis (21,571.88 Euro) is significantly higher (+86%) than that patient without sepsis (11,590.84 Euro), due to a longer (+ 163%) stay in the expensive ICU, not balanced by shorter stay in the regular ward. Also intangible costs are significantly higher: the risk for an ICU patient with sepsis to die in hospital is 3 times higher than that of an ICU patient without sepsis. In particular, those patients developing sepsis after admission are more costly and with a higher mortality risk.